Outcome of superselective bronchial artery embolization in patients with massive hemoptysis - Jijo Oommen Roy; Sridevi Rajeeve; Anna Mathew (Indian Journal of Respiratory Care, 2021)
Hemoptysis, the coughing out of blood, is a fear-provoking symptom with possible life-threatening implications such as hypotensive shock, asphyxia and, myocardial stunning. The severity of hemoptysis can range from streaky episodes to massive episodes (> 500 ml/day or > 150 ml/hour). The etiology of hemoptysis varies from lower respiratory causes such as tuberculosis, lung cancer, bronchiectasis, lung abscess, and pulmonary thromboembolism. The usual line of management is detailed history, imaging studies such as chest X-ray and CT thorax and excluding drugs affecting bleeding and clotting. Treating the underlying cause and including procoagulants usually helps to control moderate bleeding. Swift and effective management is important, especially in life-threatening cases as patients deteriorate fast. Bronchial artery embolization is indicated when conventional medical management fails and the patient is hemodynamically unstable to undergo emergency lobe/lung resection surgeries. We report our experience with four patients who presented to us with massive hemoptysis in whom superselective bronchial artery embolization (SBAE) was carried out successfully with gel-foam and coil. These patients were meticulously followed up for possible complications for one year.